2018
DOI: 10.23860/dignity.2018.03.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence on Campus: No Evidence that Studies Are Biased Due to Self-Selection

Abstract: Numerous research studies suggest that at least one in five female college students is sexually assaulted while enrolled. However, many studies exploring sexual violence prevalence on campus use methodology permitting students to self-select into the study based on interest in the topic (i.e., students receive an email offering them the opportunity to participate in a study on sexual violence). Self-selection may bias these prevalence estimates of campus sexual violence. To explore this issue, we surveyed two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…Second, we did not account for possible confounders like childhood trauma and other types of high school sexual misconduct, which may reduce the share of trauma-related symptoms that are explained by gender harassment and institutional betrayal [ 32 ]. Third, though participants were blinded to the study’s contents and therefore unlikely to be biased by self-selection, we did draw from a sample of college students, which may introduce bias and severely limit generalizability [ 17 , 33 ]. Fourth, our survey lacked attention checks, which may have inflated the reliability and degraded the validity of the data [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we did not account for possible confounders like childhood trauma and other types of high school sexual misconduct, which may reduce the share of trauma-related symptoms that are explained by gender harassment and institutional betrayal [ 32 ]. Third, though participants were blinded to the study’s contents and therefore unlikely to be biased by self-selection, we did draw from a sample of college students, which may introduce bias and severely limit generalizability [ 17 , 33 ]. Fourth, our survey lacked attention checks, which may have inflated the reliability and degraded the validity of the data [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students receive course credit for completing studies, and they are permitted to end their study participation at any time. Because of the design of the Human Subjects Pool, participants are not aware of the topic of the research prior to signing up to participate, which protects against biased self-selection [ 17 ]. This process was approved by the institution’s Office of Research Compliance (Institutional Review Board), as evidence suggests that trauma research is considered minimal risk [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In interpreting and contextualizing these findings, limitations due to measurement issues, at the intersection of sexual orientation and race, must be noted. The low survey response rate, which is typical of similar studies, can be improved but still represent student groups with minimal response bias concerns (Cook, Heath, & Thompson, 2000; Rosenthal & Freyd, 2018). Increased promotion and recruitment, especially in minority populations, would help with gaining significant statistical power to represent all groups in analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research should continue to explore the degree to which advertising that a study is about sexual assault actually does bias study samples and results. Rosenthal and Freyd (2018) recruited two samples of college women from the same university, one recruited with and one without knowledge that the study was about sexual assault, and they found nearly identical rates of victimization between the samples. Their finding suggests that sexual assault survivors are not dissuaded from participating in a study that they know is about sexual assault and, if replicated, indicates that vague recruitment language may not be as necessary as is currently believed.…”
Section: A Trauma-informed Approach To Participant Recruitmentmentioning
confidence: 99%
“…To that end, we encourage more research on how sexual assault survivors perceive different recruitment methods and specific recruitment language. Rosenthal and Freyd’s (2018) finding that transparent recruitment language may not, in fact, bias a study’s sample merits replication with both college student and community populations. In addition, research is needed on how survivors react to recruitment language that does not tell them the study will be about sexual assault: Do they feel upset, do they feel vulnerable to retraumatization when they sign up for a sexual assault study unknowingly, or do they express no such concerns?…”
Section: Conclusion: Building a Research Agenda To Inform Research Prmentioning
confidence: 99%